Lack of bedrock grain size influence on the soil production rate. (1st October 2015) - Gontier, Adrien; Rihs, Sophie; Chabaux, Francois; Lemarchand, Damien; Pelt, Eric; Turpault, Marie-Pierre
Abstract: Our study deals with the part played by bedrock grain size on soil formation rates. U- and Th-series disequilibria were measured in two soil profiles developed from two different facies of the same bedrock, i.e., fine and coarse grain size granites, in the geomorphically flat landscape of the experimental Breuil-Chenue forest site, Morvan, France. The U- and Th-series disequilibria of soil layers and the inferred soil formation rate (1–2 mm ky −1 ) are nearly identical along the two profiles despite differences in bedrock grain size, variable weathering states and a significant redistribution of U and Th from the uppermost soil layers. This indicates that the soil production rate is more affected by regional geomorphology than by the underlying bedrock texture. Such a production rate inferred from residual soil minerals integrated over the age of the soil is consistent with the flat and slowly eroding geomorphic landscape of the study site. It also compares well to the rate inferred from dissolved solutes integrated over the shorter time scale of solute transport from granitic and basaltic watersheds under similar climates. However, it is significantly lower than the denudation or soil formation rates previously reported from either cosmogenic isotope or U-series measurements from similar climates and lithologies. Our results highlight the particularly low soil production rates of flat terrains in temperate climates. Moreover, they provide evidence that the reactions of mineral weathering actually take place in horizons deeper than 1 m, while a chemical steady state of both concentrations and U-series disequilibria is established in the upper most soil layers, i.e., above ∼70 cm depth. In such cases, the use of soil surface horizons for determining weathering rates is precluded and illustrates the need to focus instead on the deepest soil horizons.